Profil Metabolik Jalur Glikogenolisis Puyuh dalam Kondisi Stres Panas dengan Pemberian Diallyl n-Sulfida (Dn-S) Organik - Mushawwir, Andi; Suwarno, Nono; Latipudin, Diding (Journal Galung Tropika, 2020)
The heat stress plays an important role for reducing feed utilization, blood profile, growth performance, and its influence performance and economic loss. Supplemented of diallyl n-sulfide of garlic is one the efforts to avoid the negative impact of heat stress. One hundred anh twenty five of female quails, 11 weeks of age, were used ini this study to investigate the impact of garlic diallyl n-sulfide (Dn-S) on metabolic of quail glycogenolysis pathway. Animal sample were obtained at 11 wk of age ramdomly assigned to five groups of treatment. Each group of treatment involved 5 replicates with 5 quails each (25 laying quails per group). All of the groups were provided basal diet and orally administered with treatements group i.e. group of thermoneutral zone (24°C) without Dn-S; group of heat stress (38°C) without Dn-S; group of heat stress (38°C) and 75 µL of Dn-S; group of heat stress (38°C) and 100 µL of Dn-S; group of heat stress (38°C) and 125 µL of Dn-S. Based on the result in this experiment showed that heat stress contibutes of the increase of glycogenolysis and metabolic compund, also enzime which is catalized its pathway. The Administered of 125 µL of Dn-S decreased glycogenolysis rate, effectivelly. In conclusion, Dn-S plays the main role to avoid exrtacelluler osmotic and metabolism fluctuation related heat stress.